Bleeding experimental model digestive system of arterial origin in the dog - Vanrell, Rafael; Grillo, Angel; Martinez, Jorge; Blanco, Edgardo; Torres, Marcos (Cirugía del Uruguay, 1975)
Through three different procedures, experimental patterns of digestive bleeding of arterial origin in dogs are assessed. The results are evaluated on the basis of angiographic studies without fast seriography. Several advantages are attained with the introduction of a terminal branch of the splenic artery in the gastric eavity, as a bleeding source.